Desenvolvimento profissional de coordenadores do NAPNE do Instituto Federal do Acre - Costa, Luana Ugalde da (2018)
The Nucleus of Assistance to People with Specific Needs (NAPNE) is the department that collaborates with the actions of inclusion of people with disabilities in the institutions of the Federal Network of Professional, Scientific and Technological Education. Understanding the importance of training NAPNE coordinators for the effective inclusion process in the Federal Institutes, this research aims to understand in which aspects the experience of an action plan of continuing education contributes to the professional development of NAPNE coordinators of the Federal Institute of Acre -IFAC. For that, we present historical and legal aspects of Special Education, using as reference the authors Pacheco and Alves (2007), Mendes (2006) and Mantoan (2006); (1999), Esteves Neto (2014), Bortolini (2012) and Nascimento, Florindo e Silva (2013); this is the inclusion of students with disabilities in the Federal Network institutions, based on the views of Kuenzer (1999); and discusses the professional development of teachers, having Day (2011), Garcia (1999) and Rodrigues (2005) as central references. The research has a qualitative character and, because of it allows the problematization of the questions concerning the daily practice of the participants and have a formative characteristic, action research was chosen as a research strategy, being carried out in four phases: diagnostic; planning; implementation and evaluation. The IFAC was chosen as a research site and the NAPNE coordinators of Rio Branco, Sena Madureira, Xapuri, Tarauacá and Cruzeiro do Sul campi participated in the research, however only one of them was able to participate in all phases of the research. Data collection techniques, interviewing and documentary analysis were used as data collection techniques. The Discursive Textual Analysis was used to analyze the data collected from the continuous training actions implemented with the participant coordinator of all research phases. From this, we show that their experience in continuing education actions contributed to the development of knowledge, skills and attitudes related to their professional performance. The training actions implemented contributed to the elaboration of the Continuing Education in Special Education for NAPNE Coordinators, the product of this research, which was evaluated for its success, merit and value by four professionals with experience in Special Education of Federal Network institutions, of the states of Bahia, Mato Grosso, Rio Grande do Norte and Rio Grande do Sul, and by a representative of the Secretariat of Professional and Technological Education (SETEC), of the Special Advisory Sector for Productive Social Inclusion and Diversity at EPT. The ad hoc evaluators issued a favorable opinion on the product, for the most part, so that the course can be considered valid in its objective of collaborating for the professional development of NAPNE coordinators and for the inclusion of students with disabilities in the Federal Network.